Improving islamic religious education learning outcomes through interactive digital media wordwall - Eli Hayati; Basnang Said (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to enhance Islamic Religious Education (IRE) learning outcomes through the use of the interactive digital medium Wordwall in a fourth-grade class at SDN Bulansari, Subang Regency, a rural school with limited technological infrastructure. A mixed-method quasi-experimental design with pre-test and post-test control groups was employed, involving 60 purposively selected fourth-grade students. Data were collected through standardized cognitive assessments, classroom observations, interviews, and focus group discussions. Quantitative data were analyzed using paired sample t-tests in SPSS, while qualitative data were examined through thematic analysis with NVivo. The findings reveal a significant improvement in the mean cognitive IRE score, from 65 (pre-test) to 82 (post-test) (p < 0.05), alongside an 85% affective engagement rate in moral values discussions. A key observation highlights Wordwall’s capacity to accelerate students’ digital literacy and reinforce the internalization of Islamic values, even within infrastructural constraints. The study concludes that Wordwall is an effective tool for improving both cognitive and character-based learning outcomes, with potential to bridge the digital divide and support